El Proyecto Hidroeléctrico de Jalcomulco, Veracruz, México, y las reacciones de la sociedad civil - León Fuentes, Nelly Josefa (Revista de historia., 2015)
This article cover one of the problems what confront the state of Veracruz over the last four years: it concerns the concessions granted to international companies for the development of various hydroelectric projects. In particular, the study takes up the case of the multi-purpose project Xalapa, situated on the Pescados River, in Jalcomulco, near the Veracruz state capital. This allows us to analyse the reactions of the inhabitants affected, and the type of conflict generated, taking into consideration their economic, social, and cultural capabilities, the resources at their disposal, and the actions of civil organisations. Analysis rests on environmental history, employing oral history as a strategy given that resistence is ongoing and actors’ testimonies are fundamental for an overall understanding of the processes of apropriation and dispossession: this route allows the ‘excluded’ to be heard.